Carvedilol Attenuates Inflammatory-Mediated Cardiotoxicity in Daunorubicin-Induced Rats - Punniyakoti T. Veeravedu; Makoto Kodama; Vivian Soetikno; Kenji Suzuki; Rajarajan A. Thandavarayan; Kenichi Watanabe; Flori R. Sari; Wawaimuli Arozal; Somasundaram Arumugam; Meilei Harima (MDPI AG, 2011)
Cardiotoxicity, which results from intense cardiac oxidative stress and inflammation, is the main limiting factor of the anthracyclines. Carvedilol, a beta blocker that is used as a multifunctional neurohormonal antagonist, has been shown to act not only as an anti-oxidant, but also as an anti-inflammatory drug. This study was designed to evaluate whether carvedilol exerts a protective role against inflammation-mediated cardiotoxicity in the daunorubicin (DNR)-induced rats. Carvedilol was administered orally to the rats every day for 6 weeks at a cumulative dose of 9 mg/kg body weight DNR. DNR significantly induced cardiac damage and worsened cardiac function as well as increased cardiac mast cell density, elevating the myocardial protein and mRNA expression levels of tumor necrosis factor-α, vascular cell adhesion molecule-1, inter-cellular adhesion molecule-1, nuclear factor kappa-B, cyclooxygenase-2, monocyte chemotactic protein -1 and interleukin -6 compared to that in the control group. Cotreatment with carvedilol significantly attenuated the myocardial protein and mRNA expression levels of these inflammatory markers, decreased cardiac mast cell density, improved histological cardiac damage and cardiac functions. In conclusion, inflammation plays a significant role in DNR-induced cardiotoxicity, and carvedilol contributes to cardioprotection against inflammation-mediated cardiotoxicity in DNR-induced rats through its anti-inflammatory mechanism.